2001
DOI: 10.1016/s0379-0738(01)00524-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatal poisoning in drug addicts in the Nordic countries

Abstract: The study includes medicolegally examined fatal poisonings among drug addicts in 1997 in the five Nordic countries: Denmark, Finland, Iceland, Norway and Sweden, and the results are compared to a similar investigation from 1991. A common definition of "drug addict" was applied by the participating countries. The highest death rate by poisoning in drug addicts was observed in Denmark, where it was 6.54 per 10(5)inhabitants, followed by Norway with 6.35, Sweden with 2.21, Finland with 1.63 and Iceland with 1.20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 3 publications
2
36
0
4
Order By: Relevance
“…The distribution of drugs causing fatal poisonings varies depending on the region. In Nordic countries poisoning among drug addicts take the first place in fatal poisonings (46,47). Steentoft et al (46) reported that the greatest number of drug addict deaths in Nordic countries was seen in Denmark, followed in descending order by Norway, Sweden, Finland and Iceland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of drugs causing fatal poisonings varies depending on the region. In Nordic countries poisoning among drug addicts take the first place in fatal poisonings (46,47). Steentoft et al (46) reported that the greatest number of drug addict deaths in Nordic countries was seen in Denmark, followed in descending order by Norway, Sweden, Finland and Iceland.…”
Section: Discussionmentioning
confidence: 99%
“…In Nordic countries poisoning among drug addicts take the first place in fatal poisonings (46,47). Steentoft et al (46) reported that the greatest number of drug addict deaths in Nordic countries was seen in Denmark, followed in descending order by Norway, Sweden, Finland and Iceland. In Denmark, Norway and Sweden heroin and morphine was the most frequently encountered drug (47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of fatal carisoprodol intoxications have also reported frequent detection of additional drugs [17,21]. A large degree of polydrug abuse is also reported from fatal intoxications with other drugs, where an average of 2.4-3.5 drugs are found [35,36], as well as studies of drugged drivers showing an average number of 2.6 additional drugs [37].…”
Section: Discussionmentioning
confidence: 99%
“…They are a valuable indicator of dimensions of the drug abuse problem in a country or a region, especially when interpreted along with other indicators (1,2). Studies have shown that, similarly to other mortality causes (3)(4)(5), certification of drug abuse deaths presents a significant problem in the world, whether they are overdose related deaths or other deaths resulting from drugs misuse (6,7).…”
Section: Introductionmentioning
confidence: 99%